Japanese Encephalitis Virus Vaccination Elicits Cross-Reactive HLA-Class I-Restricted CD8 T Cell Response Against Zika Virus Infection - Tarbe, Marion; Dong, Wei; Hu, Guang; Xu, Yongfen; Sun, Jing; Grayo, Solene; Chen, Xianyang; Qin, Cheng-Feng; Zhao, Jincun; Liu, Li; Li, Xiuzhen; Leng, Qibin (Frontiers in Immunology, 2020)
Japanese encephalitis virus (JEV) exposure or vaccination could elicit cross-reactive CD8 T cell immunity against heterologous flaviviruses in humans. In addition, cross-reactive CD8 T cells induced by dengue virus (DENV) have been shown to play a protective role against Zika virus (ZIKV). However, how JEV exposure or vaccination affects ZIKV infection in humans remains unclear. In this report, epitope prediction algorithms were used to predict the cross-reactive CD8 T cell epitope restricted to human HLA between JEV and ZIKV. We found that these predicted CD8 T cell epitopes are immunogenic and cross-reactive in humanized HLA transgenic mice. Moreover, JEV vaccine immunization provided cross-protection against ZIKV infection. Furthermore, CD8 T cells were involved in the protection against ZKIV infection in vivo. Our results have an important clinical implication that vaccination with JEV SA14-14-2 may provide protection against ZIKV infection in humans.